Frequency and Genotype Diversity of Human Pegiviruses - Yucebag-Duranay, Ebru; Kocazeybek, Bekir Sami; Kuskucu, Mert Ahmet (Infectious diseases & clinical microbiology, 2025)
Objective: Human pegiviruses (HPgV) belong to the Flaviviridae family. They were initially considered hepatotropic viruses, but later, epidemiological studies showed no connection with acute or chronic hepatitis. This study included frozen and stored plasma samples of HIV-infected, ART-naive patients, which were routinely sent to Cerrahpasa Faculty of Medicine, Molecular Microbiology Laboratory for HIV RNA detection and HIV drug resistance analysis between January and September 2019. Materials and Methods: The study analyzed plasma samples of HIV-infected, antiretroviral therapy-naive patients and control serum samples. HPgV RNA in the samples was investigated using the RT-nested PCR method, and primer sets designed from the 5'UTR region were used for amplification and genotyping using Sanger sequencing. Results: A total of 117 plasma samples from HIV-infected, antiretroviral therapy-naive patients and 100 control serum samples were included in the study. HPgV-1 RNA was detected in 24.78% of the patient group and 18% of the control group (p=0.2264). HPgV-2 RNA was not detected in any groups. Phylogenetic analysis showed that all HPgV-1 strains isolated were genotype 2; the subgroup was commonly 2a (95.56%). Only two of the 29 strains belonging to the patient group were subtype 2b (4.44%). There was no statistically significant difference between HPgV-1 infected and uninfected HIV-1-positive subjects regarding the HIV-1 viral loads. HPgV-1 positivity rates were higher in those aged <40 years (25.80%) than in those aged [greater than or equal to]40 years (16.12%) (p=0.00044). Conclusion: Genotype 2a was identified as the dominant genotype, and this finding is consistent with previous studies reported from Tiirkiye and other countries in the same geographical region. Further studies are needed to understand better the effects of the HPgV-1 virus on HIV infection. Keywords: HIV, HPgV-1, HPgV-2, GBV- C / HGV, genotyping